Long-Term Safety of Topical Bacteriophage Application to the Frontal Sinus Region - Drilling, Amanda J.; Ooi, Mian L.; Miljkovic, Dijana; James, Craig; Speck, Peter; Vreugde, Sarah; Clark, Jason; Wormald, Peter-John (Frontiers in Cellular and Infection Microbiology, 2017)
Background Staphylococcus aureus biofilms contribute negatively to a number of chronic conditions, including chronic rhinosinusitis (CRS). With the inherent tolerance of biofilm-bound bacteria to antibiotics and the global problem of bacterial antibiotic resistance, the need to develop novel therapeutics is paramount. Bacteriophage (“phage”) therapy has previously shown promise in treating sinonasal S. aureus biofilms. Methods This study investigates the long term (20 days) safety of topical sinonasal flushes with bacteriophage suspensions. The bacteriophage cocktail NOV012 against S. aureus selected for this work contains two highly characterized and different phages, P68 and K710. Host range was assessed against S. aureus strains isolated from CRS patients using agar spot tests. NOV012 was applied topically to the frontal sinus region of sheep, twice daily for 20 days. General sheep wellbeing, mucosal structural changes and inflammatory load were assessed to determine safety of NOV012 application. Results NOV012 could lyse 52/61 (85%) of a panel of locally derived CRS clinical isolates. Application of NOV012 to the frontal sinuses of sheep for 20 days was found to be safe, with no observed inflammatory response or tissue damage. Conclusion. NOV012 cocktail appears safe to apply for extended periods to sheep sinuses and it could infect and lyse a wide range of S. aureus CRS clinical isolates. This indicates that phage therapy has strong potential as a treatment for chronic bacterial rhinosinusitis.